A Web-Based Diploma Service Management Information System - Riska Damayanti; Siti Sufaidah (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Manual diploma service management often causes delays and limits students in obtaining real-time information about their application status. This study aims to design and implement a web-based diploma service management system that provides integrated and accessible administrative services. The system supports multiple user roles, allowing students to submit diploma requests, upload required documents, and monitor application status, while administrators verify documents and validate academic data. The development process follows a structured software development method consisting of requirement analysis, system design, implementation, testing, and maintenance. Functional testing shows that all system features operate according to user needs. The resulting system enables structured diploma processing, accurate data verification, real-time status monitoring, and secure digital record management. The implementation of this system improves efficiency, accuracy, and accessibility of diploma services and supports the digital transformation of academic administration.